Justification of inflationary trends in the context of social and macroeconomic development of the national economy of Ukraine - Dedilova, T.; Nesterenko, V.; Prokopenko, M.; Деділова, Т. В.; Нестеренко, В. Ю.; Прокопенко, М. В. (Харківський національний автомобільно-дорожній університет, 2023)
Purpose. The purpose of the study is analyzing the reasons for the deepening of the inflation process in Ukraine at the present stage and justification of inflationary trends in the context of social and macroeconomic development of the national economy of Ukraine. Methodology of research. The theoretical and methodological bases of the study were the works of leading domestic and foreign scientists devoted to the inflation as a factor in the development of the national economy. The method of theoretical generalization; method of analysis and synthesis; graphical methods were used in the study. Findings. Based on the results of the study, the factors of influence on inflationary processes in the context of social and macroeconomic development of the national economy of Ukraine are actualized. The patterns of development of inflationary processes in Ukraine in the period from 2000-2023 are determined. In the pre-war period of recent years, such a regularity of the inflationary process as the fear and panic of the population regarding the fact that the national currency will soon completely lose its purchasing power became characteristic of Ukraine. Also, the increase in the level of inflation in Ukraine is constantly intensified by the imbalance of state revenues and expenditures, the presence of a budget deficit; extensive use of domestic borrowing to cover the budget deficit. In addition, as a result of military operations in the country, the prices of consumer goods, which belong to strategic and socially significant groups of goods (fuel, groceries, hygiene products, pharmaceuticals, etc.), have increased significantly. Originality. The scientific and theoretical approach to managing inflationary processes in Ukraine was further developed through a retrospective analysis and actualization of inflationary forms in the context of social and macroeconomic development of the national economy of Ukraine in the wartime. Practical value. The practical value of the study is the possibility of using its results to develop strategic and tactical monetary policy decisions aimed at stimulating economic development while maintaining low inflation.
Обґрунтування інфляційних тенденцій в контексті соціального та макроекономічного розвитку національної економіки України
Keywords: inflation; forms; factors; social sphere; macroeconomics; national economy; development; інфляція; форми; фактори; соціальна сфера; макроекономіка; національна економіка; розвиток; 338.22; 10.30977/PPB.2226-8820.2023.31.46